International Circumpolar Surveillance System for Invasive Pneumococcal Disease, 1999–2005 - Michael G. Bruce (Emerging Infectious Diseases, 2008)
The International Circumpolar Surveillance System is a population-based surveillance network for invasive bacterial disease in the Arctic. The 7-valent pneumococcal conjugate vaccine (PCV7) was introduced for routine infant vaccination in Alaska (2001), northern Canada (2002–2006), and Norway (2006). Data for invasive pneumococcal disease (IPD) were analyzed to identify clinical findings, disease rates, serotype distribution, and antimicrobial drug susceptibility; 11,244 IPD cases were reported. Pneumonia and bacteremia were common clinical findings. Rates of IPD among indigenous persons in Alaska and northern Canada were 43 and 38 cases per 100,000 population, respectively. Rates in children <2 years of age ranged from 21 to 153 cases per 100,000 population. In Alaska and northern Canada, IPD rates in children <2 years of age caused by PCV7 serotypes decreased by >80% after routine vaccination. IPD rates are high among indigenous persons and children in Arctic countries. After vaccine introduction, IPD caused by non-PCV7 serotypes increased in Alaska.